2015
DOI: 10.2319/100514716.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wearing fixed orthodontic appliances on quality of life among adolescents: Case-control study

Abstract: Adolescents who wore fixed orthodontic appliances had a greater chance of reporting a negative impact on OHRQoL than those who did not wear such appliances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…4 Wearing multibonded orthodontic appliances has a temporary negative impact on patients' QoL. 5,24 The negative impacts are greater in females than in males. 25 More than a two times deterioration of OHIP-14 score was observed in this study at the end of 1 month of treatment compared to pretreatment levels.…”
Section: Discussionmentioning
confidence: 99%
“…4 Wearing multibonded orthodontic appliances has a temporary negative impact on patients' QoL. 5,24 The negative impacts are greater in females than in males. 25 More than a two times deterioration of OHIP-14 score was observed in this study at the end of 1 month of treatment compared to pretreatment levels.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, características clínicas como má oclusão, traumatismo, cárie dental e fluorose provocam impactos na qualidade de vida dos adolescentes 24 . Esta revisão integrativa encontrou que a cárie dentária e outros problemas bucais, como a fluorose, higiene bucal, problemas periodontais, quando estudada como aspecto clínico principal, não exerceram influência sobre a qualidade de vida dos adolescentes pesquisados, no entanto, a dor orofacial emergiu como uma condição que está diretamente associado à má qualidade de vida 26,27,16 .…”
Section: Discussionunclassified
“…Uma vez que a pirâmide de hierarquia da evidência 13 não inclui estudos transversais nem testes de validação, apenas dois estudos 24,27 puderam ser classificados por esse sistema obtendo nível de evidência III e IV respectivamente. A ausência de ensaios clínicos randomizados investigando a saúde bucal e a qualidade de vida de adolescentes revela a necessidade da realização de novos estudos focalizados nessa temática, com amostras maiores e representativas, e por períodos mais longos de acompanhamento, possibilitariam esclarecer algumas peculiaridades, como: estilo de vida, hábitos, fatores psicológicos, práticas de higiene bucal, tabagismo e consumo de álcool, auxiliando assim avaliar o impactado destes na qualidade de vida dos adolescentes 23 .…”
Section: Discussionunclassified
“…The questionnaire was administered as an interview as some previous studies had concluded that 8year-olds have difficulty completing the questionnaire on their own [20] and the scores of the subscales and overall score on the CPQ8-10 were significantly higher in the group of children who responded to the interviewer-administered measure, not compromising the results [21].…”
Section: Figure 1 Methodology Flowchartmentioning
confidence: 99%